Improvements in diabetic albuminuria and podocyte differentiation following Roux-en-Y gastric bypass surgery. (January 2020) - Canney, Aoife L; Cohen, Ricardo V; Elliott, Jessie A; M Aboud, Cristina; Martin, William P; Docherty, Neil G; le Roux, Carel W
Background: Multiple studies demonstrate an albuminuria-lowering impact of Roux-en-Y gastric bypass surgery, but neither evaluation of its penetrance across different baseline levels of albuminuria nor its association with alterations in podocyte phenotype has previously been reported. Methods: We profiled changes in body weight, glycaemic control and urinary albumin excretion following Roux-en-Y gastric bypass surgery in 105 patients with type 2 diabetes, albuminuria of varying degrees of severity and classified as being at moderate or high risk of chronic kidney disease progression according to the Kidney Disease: Improving Global Outcomes 2012 criteria. In parallel pre-clinical studies, the impact of Roux-en-Y gastric bypass surgery on markers of podocyte injury was assessed in the Zucker diabetic fatty rat model of diabetic kidney disease. Results: At 12- to 18-month post-operative follow-up in patients at moderate or high risk of chronic kidney disease, significant reductions in albuminuria were observed across all tertiles of baseline albumin–creatinine ratio, with remission of albuminuria occurring in 78% of patients. Relative to sham-operated control animals, weight loss and improvements in glycaemia following Roux-en-Y gastric bypass surgery in Zucker diabetic fatty rats were paralleled by normalisation of glomerular tuft-size, reductions in podocyte expression of desmin, and preservation of podocyte foot process morphology. Conclusion: Improvements in podocyte differentiation likely underpin the reductions in albuminuria observed following Roux-en-Y gastric bypass surgery.